2002
DOI: 10.1002/ijc.10261
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin induces angiogenesis of murine neuroblastoma cells in mice

Abstract: Angiogenesis is an essential process for tumor growth and is regulated by tumor-derived angiogenic cytokines. Osteopontin (OPN) is one of the cytokines produced by various tumor cells and is suggested to be involved in angiogenesis by upregulating endothelial cell migration in cooperation with vascular endothelial cell growth factor (VEGF). To provide evidence of OPN involvement in a causal role in tumor angiogenesis, we generated a stable transfectant from murine neuroblastoma C1300 cells to constitutively se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 30 publications
3
60
0
2
Order By: Relevance
“…[16][17][18][19] OPN enhances tumoral cell proliferation increasing the malignant phenotype 16,17,25,26 and its downregulation in cancer cells reduces their growth and tumorigenicity in mice. 27 In line with these observations we found that OPN enhances HMCLs proliferation and increases IL-6 proproliferative effect on myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] OPN enhances tumoral cell proliferation increasing the malignant phenotype 16,17,25,26 and its downregulation in cancer cells reduces their growth and tumorigenicity in mice. 27 In line with these observations we found that OPN enhances HMCLs proliferation and increases IL-6 proproliferative effect on myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…7,13 Recent data indicate that OPN also stimulates endothelial cell survival and migration [13][14][15] and acts as a potent proangiogenic factor in vivo. 16,17 In several solid tumors it has been shown that OPN is overexpressed and promotes tumoral growth, angiogenesis and progression. 18,19 Recently, high OPN levels have been demonstrated in MM patients; therefore, OPN production by BM mononuclear cells or by myeloma cells has been hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…It is well described that Opn enhances non-haemopoietic tumour cell proliferation increasing the malignant phenotype (Takahashi et al, 2002;Hirama et al, 2003;Angelucci et al, 2004). Furthermore, downregulation of Opn in cancer cells reduces growth and tumorigenicity in mice (Behrend et al, 1994).…”
Section: Osteopontin and Aberrant Haemopoiesismentioning
confidence: 97%
“…Osteopontin Osteopontin (OPN) is a pro-angiogenic factor that promotes endothelial cell migration and survival [60][61][62][63][64][65][66][67][68][69][70], adhesion of both endothelial and smooth muscle cells [71], and has been associated with tumoral angiogenesis in mouse models [72,73]. OPN is produced directly by myeloma cells and is critical for the stimulation of endothelial cells.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%